Синхронізація генераторів та їх застосування - Лапошина, О. К. (ХНУРЕ, 2019)
The ability to precisely form oscillations of various frequencies and shapes, easily and conveniently changing their parameters, is a key requirement in a wide range of very different areas, for example, in medicine, industry, measuring equipment, and the defense industry. Communication systems require synchronization of signals, which consists in establishing and maintaining accu-rate temporal correspondence formed in the transmitting part and signals re-ceived in the receiving part.